Nekatere razsežnosti nasilne viktimizacije - Meško, Gorazd (Teorija in praksa, 1998)
The author introduces some main findings in victimology and compares them with attempts of movement for victims of criminal offence. Classical criminology often overlooks a role and position of victim. Victimological research analysis on interaction between perpetrator and victim went even so far that it was impossible to distinguish between those two. The article in particular emphasizes some findings on a smaller proportion of victims of criminal offence and their close relatives, who suffer intense psychological consequences, potentially having omnious difficulties with social functioning. Three 'sorts' of victims of burglary, robbery and rape are introduced. Special attention is given to the questions regarding a victim during a trial process, emphasizing the instrumental role of the victim during the trial process, when he/she is not defined in terms of 'victim', but rather being a state's instrument for proving the accused guilty. This causes indignation and criticism with adherents of movememnt for vicitms.
Keywords: viktimizacija; viktimologija; kriminologija; kazenski postopek; kazensko pravo; criminal law